1975
DOI: 10.1111/j.1432-1033.1975.tb02203.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequences of Escherichia coli 16‐S RNA Associated with Ribosomal Proteins S7, S9, S10, S14 and S19

Abstract: A ribonucleoprotein fragment containing proteins S7, S9, S10, S14, and S19 was isolated in high yield from Escherichia coli 30‐S ribosomal sub‐particles. The same fragment was obtained whether ribosomes from E. coli strain A19 or MRE 600 were used, despite the fact that protein S7 differs widely between the two strains. RNA was extracted from this fragment and fractionated on gels containing 7 M urea, to reveal “hidden breaks”. A well‐defined and reproducible pattern of RNA fragments was obtained, with the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0

Year Published

1975
1975
2003
2003

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 25 publications
5
69
0
Order By: Relevance
“…As before (3) two second dimension gels were made for each first dimension gel strip, the upper half of the latter being run on a 10% second dimension gel, and the lower half on a 20% gel. After electrophoresis, the cross-linked complexes were located on the gels by autoradiography, and were extracted in the usual manner (17). In one case (complex E, see results), the isolated complex was further-digested with ribonuclease T1 in the presence of 50 4g of unlabelled carrier tRNA, followed by separation on a second two-dimensional gel, exactly as described pre (18), and in some cases tertiary digestions were made, as described (4).…”
Section: Methodsmentioning
confidence: 99%
“…As before (3) two second dimension gels were made for each first dimension gel strip, the upper half of the latter being run on a 10% second dimension gel, and the lower half on a 20% gel. After electrophoresis, the cross-linked complexes were located on the gels by autoradiography, and were extracted in the usual manner (17). In one case (complex E, see results), the isolated complex was further-digested with ribonuclease T1 in the presence of 50 4g of unlabelled carrier tRNA, followed by separation on a second two-dimensional gel, exactly as described pre (18), and in some cases tertiary digestions were made, as described (4).…”
Section: Methodsmentioning
confidence: 99%
“…[6][7]), and several of these fragments have been found to contain S7. Further, it has recently been shown that S7 is the only 30-S protein which can be specifically cross-linked to any large extent to RNA by irradiation with ultraviolet light [8].…”
mentioning
confidence: 99%
“…P. Ebel for helpful discussions throughout the course of' this work, and to Miss M. Delfau for her technical assistance. The work was financially supported by the Centre Nurional dr 10 Recherche Scirntifique and by the Delegation GPntWe a la Ri,chcrc,hc …”
mentioning
confidence: 99%